ANALISIS PENGUKURAN KINERJA SMK NEGERI 6 SURAKARTA DENGAN PENDEKATAN BALANCED SCORECARD - Mahasiswa Magister Akuntansi FE UNS, Joko Pramono (MAJALAH ILMIAH GEMA, 2014)
The study aims to measure the performance of SMKN 6 Surakarta by Balanced Scorecard approach. It is a quantitative study with descriptive design. The study was conducted by measuring the level performance of SMKN 6 Surakarta on four aspects (perspectives) performance in the Balanced Scorecard, namely: financial perspective, customer perspective, internal business processes, and learning and growth perspective. The primary data which is questionnaire was used to measure both the performance of customer perspective and learning and growth perspective, while the secondary data was used to measure both the financial perspective performance and internal business process perspective. The study used students and teachers and also staffs of SMKN 6 Surakarta as respondents. The final result of the study shows that the performance of SMKN 6 Surakarta is on the very good level in general. The performance of financial perspective shows good performance which qualifies the requirement of economical, effective, and efficient, while the performance of customer perspective gains good category. In addition, the performance of internal business processes shows very good level and also the performance of learning and growth perspective shows good category. The results recommend SMKN 6 Surakarta to (1) make effort to improve the school performance which has been at the good level into very good category, (2) the staffs and the librarian should improve the service quality to students, (3) the teachers should concern much more toward the problem of studentâs learning, (4) the school leader should be more accommodative and creative in dealing with any school problems, so that the performance of SMKN 6 Surakarta will improve. Keywords: performance measurement, Balanced Scorecard, financial perspective, customer perspective, process of internal business perspective, learning and growth perspective.